A Dual Mechanism of Cognition and Emotion in Processing Moral-Vertical Metaphors - Zhai, Dongxue; Guo, Yaling; Lu, Zhongyi (Frontiers in Psychology, 2018)
A moral concept involves two main factors: moral cognition (indicated by morality) and emotion (indicated by emotionality). The cognitive mechanism underlying moral metaphors on the vertical dimension (e.g. moral-up, immoral-down) was investigated in 3 experiments using implicit association tests. The results of Experiment 1 show a stronger association of "moral-up, immoral-down" between words high in morality and vertical space than between words low in morality and vertical space, which shows that cognitive factors of morality facilitate the processing of vertical spatial metaphors of moral concepts. Experiment 2, employing moral words different in emotionality, reveals a stronger association of "moral-up, immoral-down" between words high in emotionality and vertical space than between words low in emotionality and vertical space, which shows that emotional factors of morality facilitate the processing of vertical spatial metaphors of moral concepts. A comparison between the two experiments suggests a faster response to emotion than to moral cognition and similar association strengths of the two factors with verticality. Using words high in morality and emotionality, Experiment 3 shows that a combination of the two conditions (i.e., high morality and high emotionality) leads to a stronger tie with verticality than either condition. The above three experiments indicate that both moral cognition and emotion facilitate the processing of vertical spatial metaphor of moral concepts, and the forces of the two, which jointly affect the metaphorical connection between morality and verticality, are basically equal, although the processing of emotionality is faster than that of morality.